A Sol-solvothermal Processed 'Black TiO2' as Photoanode Material in Dye Sensitized Solar Cells. (October 2017) - Ullattil, Sanjay Gopal; Thelappurath, Aiswarya Vijayakumar; Tadka, Sriman Narayana; Kavil, Jithesh; Vijayan, Baiju Kizhakkekilikoodayil; Periyat, Pradeepan
Graphical abstract: Highlights: The first Mn 2+ assisted sol-solvothermal strategy for the synthesis of black TiO2 . New anatase peak formation as Mn (II) incorporated in to the TiO2 sol. Implemented black TiO2 alone as photoanode material in DSSC. NIR absorbing black TiO2 possessed 79% greater efficiency than the P25-TiO2 . Abstract: A sol-solvothermal synthetic strategy has been designed and executed for the preparation of black TiO2 nanoparticles and has been implemented as photoanode in dye sensitized solar cell (DSSC) for the first time. As synthesized yellow anatase titania (YAT) possessed visible light absorption and the black anatase titania (BAT) exhibited a longer wavelength absorption even at the IR region of the solar spectrum. These visible light absorbing YAT and the IR absorbing BAT nanoparticles have been employed as photoanode in dye sensitized solar cell (DSSC) and performance have been compared with DSSC fabricated using commercially available titania, P25. Distinctly, the efficiency of the IR absorbing black anatase TiO2 has been found 50% greater than the yellow anatase TiO2 (YAT) and 79% greater than the commercially available P25.